Some observations on Nothapodytes foetida: An overview - Namdeo, Ajay G.; Sharma, A.; Mahadik, K.R. (Pharmacognosy Reviews)
Nothapodytes foetida is a medium size tree distributed in Western Ghats of India, is considered to be an endangered species. Phytochemical studies of the drug revealed the presence of camptothecin, hydroxy camptothecin, acetyl camptothecin, methoxy camptothecin, steroids and fatty acids. The highest concentration of camptothecin (CPT) is found in young immature fruits. Tissue culture studies of the drug show that a lot of hormones (naphthalene acetic acid, benzyl amino purine (BAP), 2, 4- dichloro phenoxy acetic acid (2,4,D), thidiazuron (TDZ), 2, 4, 5-trichlorophenoxy acetic acid (2,4,5 T) and picloram enhance CPT content. The most important combination affect callus induction and CPT content are 2, 4-D with BAP and 2, 4, 5-T with NAA in one month old callus. At concentration (1.36 µM) TDZ simulate shoot formation (46.25%). Camptothecin and 9- methoxycamptothecin have promising anti-cancer activity. The molecular target of camptothecin is inhibiting the nuclear enzymes topoisomerase I DNA complex. Camptothecin inhibits Tat-mediated transactivation of HIV-1 LTR, a potential target for therapy of HIV-1 infection. Camptothecin itself is not used clinically due to its cytotoxicity, but its derivatives (irinotecan and topotecan) are most effective for the treatment of cancer.
Keywords: Camptothecin; Mappia foetida; Anticancer; Murashige and skoog medium; Callus